Additive manufacturing of PEEK-based continuous fiber reinforced thermoplastic composites with high mechanical properties. (April 2023) - Barış Vatandaş, Bahri; Uşun, Altuğ; Yıldız, Nuri; Şimşek, Cemaleddin; Necati Cora, Ömer; Aslan, Mustafa; Gümrük, Recep
Highlights: CFRTP composites with high fiber volume fraction were manufactured. An infrared heater was utilized in printing process to improve interlayer bonding. The mechanical properties of CFRTP specimens were characterized. Superior mechanical performance was obtained in tensile and flexural testing. Abstract: Continuous fiber-reinforced thermoplastic (CFRTP) printing is a promising method to increase the mechanical properties of FDM printed parts. In this study, it was aimed to achieve high mechanical properties using PEEK as a matrix and carbon fiber as support material. For this purpose, a novel production line was used to achieve CFRTP filaments with adjustable fiber volume fractions, and samples were additively manufactured. Furthermore, an infrared heater was utilized to improve the interlaminar bonding of the printed samples. Although not affecting the tensile properties, usage of an infrared heater yielded a significant improvement in three-point bending tests due to shear forces. Furthermore, increasing the fiber volume fraction excessively showed a decrease in the flexural strength of the printed parts because of the insufficient wetting of the fibers and porosities occurring during the printing process. Lastly, failure surfaces of the printed parts and printed part cross-sections were examined.